KINERJA BADAN NARKOTIKA NASIONAL PROVINSI SULAWESI TENGAH - Hartini, Hartini (Katalogis, 2020)
The National Narcotics Agency of Central Sulawesi province with the task of preventing, eradicating, misusing and illicit drug trafficking needs to be addressed throughout the society, addressing this, it is expected that all elements of society will cooperate in prevention, eradication and illicit drug trafficking, so that the vision of the National Narcotics Agency of Central Sulawesi province will be realized to realize the Central Sulawesi net of narcotics in 2017. The objective of this research is to find out the performance of National Narcotics Agency of Central Sulawesi province had not been run effectively and efficiently which was reviewed based on Dwiyanto's organizational performance theory model using variables: 1). Productivity, 2). Quality of Service, 3). Responsibility, 4). Responsiveness, 5). Accountability. The type of research used was qualitatively with the number of informants was 5 people selected by purposive sampling. The data were collected through observation, interview and documentation by analyzing the results of all interviews. The results of the research show that the performance of National Narcotics Agency of Central Sulawesi province has not been fully optimized. Seen from the five performance criteria refers to Dwiyanto, the criteria that run well were productivity, quality of service, responsibility, and accountability. While the criteria is not optimal on the performance of National Narcotics Agency of Central Sulawesi province is responsiveness there are some obstacles faced by the rehabilitation sector where there are still rehabilitation institutions that have been given reinforcement but have not yet operated, while for the target number of abusers, victims of abuse and narcotics addicts who undergo post-rehabilitation services have not yet proceeded properly.